Potential Roles of the Retinoblastoma Protein in Regulating Genome Editing - Jiang, Yuning; Chu, Wai Kit (Frontiers in Cell and Developmental Biology, 2018)
Genome editing is an important tool for modifying genomic DNA through introducing DNA insertion or deletion at specific locations of a genome. Recently CRISPR/Cas9 has been widely employed to improve the efficiency of genome editing. The Cas9 nuclease creates site-specific double strand breaks (DSBs) at targeted loci in the genome. Subsequently, the DSBs are repaired by two pathways: Homologous Recombination (HR) and Non-Homologous End-Joining (NHEJ). HR has been considered as “error-free” because it repairs DSBs by copying DNA sequences from a homologous DNA template, while NHEJ is “error-prone” as there are base deletions or insertions at the breakage site. Recently, RB1, a gene that is commonly mutated in retinoblastoma, has been reported to affect the repair efficiencies of HR and NHEJ. This review focuses on the roles of RB1 in repairing DNA DSBs, which have impacts on the precision and consequences of the genome editing, both at the targeted loci and the overall genome.